Comparison of Ozonation and Catalytic Ozonation Processes for the Decolourization of Reactive Red 195 Azo Dye in Aqueous Solution - Gul, Sermin; Bahar, Gonca; Ozcan Yildirim, Ozlem (Asian Journal of Chemistry, 2010)
Reactive red 195 (RR195) triazine containing azo dye was treated by ozone (O3) and ozone combined with granular activated carbon (O3/GAC) processes. Effects of pH and amount of catalyst on treatment efficiency were examined. At ambient temperature and pH 11, the decolourization efficiency of ozone oxidation was 99.61 % within 0.5 h. However under the same conditions, the decolourization efficiency of GAC catalytic ozonation process reached to 99.71 %. The effect of t-butanol (TBA) of 1 mM as radical scavenger on the O3 and O3/GAC processes suggests that the decolourization reaction in O3/GAC process proceeds by mainly radical type mechanism whereas O3 process proceeds by molecular ozone. FTIR was used for characterization of untreated dye and degradation products obtained after catalytic ozonation. The microstructures of the activated carbons obtained before and after ozonation process were examined by scanning electron microscope.